Exploring the association between body mass index and dental caries in 3–7-year-old children, living in Łódź, Poland - Bruzda-Zwiech, Agnieszka; Borowska-Strugińska, Beata; Filipińska, Renata; Żądzińska, Elżbieta; Lubowiedzka-Gontarek, Beata; Szydłowska-Walendowska, Beata; Wochna-Sobańska, Magdalena (Anthropological Review, 2017)
Dental caries and childhood obesity are major problems affecting the health of children and preventing these conditions in children have been recognized as public health priorities (Hong et al. 2008; Odgien et al. 2010). The aim of the present study was to analyze the association between age-specific body mass index (BMI-for age) and dental caries in 3- to 7-year-olds. A cross-sectional study was conducted on 729 children from randomly chosen kindergartens and elementary schools in the urban area of Lodz, Poland. Anthropometric measurements were taken and the BMI-for-age was calculated for each child. Dental examinations were performed according to the WHO criteria. The sum of decayed, missing, filled primary/ permanent teeth and surfaces - dmft/DMFT and dmft/DMFTS, and caries prevalence were computed. The percentage distribution of the BMI categories in the study group was: 72.7% normal weight, 8.92% underweight, 12.89% overweight and 5.49% obese. Caries prevalence in the primary dentition was significantly lower in underweight children than in those who were of normal weight (p=0.004) or were overweight (p=0.039). However, controlling for age and gender, no significant association was noted between BMI and caries prevalence in either dentition group. The Kruskal-Wallis test failed to reveal any significant differences in mean dmft across the four BMI groups in the whole population, nor within particular age groups, nor in DMFT in 5- to 7-year-olds. There was no association between BMI and dental caries either in the primary dentition or permanent teeth in the early period after eruption.